Kill it to save it – An Autopsy of Capitalism’s Triumph over Democracy - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2017)
This article reviews the book, "Kill it to save it – An Autopsy of Capitalism’s Triumph over Democracy," by Corey Dolgon.